Dari Nalar Literalis-Normatif Menuju Nalar Kontekstualis-Historis dalam Studi Islam - Thahir, A. Halil (ISLAMICA: Jurnal Studi Keislaman, 2010)
It seems legitimate to say that the classical-conventional methodology gives birth to a rigid and theo-centric view of Islam. This form of methodology is dogmatic and is replete with a systematic indoctrination, such that would lead one to accept a particular view of religion often blindly while believing that other views are wrong. This paper offers a challenge to that old-fashion methodology by deconstructing it, and then constructing a new form of methodology. We treat the classical methodology as being literal-normative, and the new one that we propose as being contextual-historical. We argue that the former has gone out of context, because it was invented for its own time. The latter in the meantime is critical and considerate to new demands and contexts. We speak of this new methodology as characteristically multi-disciplin-ary in the sense that within its premises, various forms of knowledge are deemed to have been interconnected and together constitute an integral web of epistemic construction.